A study of the macroeconomic effects of China's fiscal deficits - Xu, Xiongqi 1972-; Xie, Fei (Enrich series on China's economic issues, 2011)
Divided into four parts, this consideration establishes a theoretical framework that analyzes the large-scale effects of China's fiscal deficits. A detailed review, this account discusses a variety of topics, including policy sustainability, national savings, nominal interest rates, money supply, inflation, and balance of trade. In addition, this empirical study evaluates the implications China's fiscal deficit policy on macroeconomic regulation and control function.